Development and application of novel virtual High Throughput Screening (vHTS) Technologies - Carta, Giorgio (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2008)
The development of new pharmaceutical drugs is an expensive, timeconsuming task with an often low success rate. Traditionally, once a therapeutic target and its role in disease is identified, the process of identification of new drugs was performed through combinatorial chemistry. This is a technique for rapidly and systematically assembling a variety of molecular entities, or building blocks, in many different combinations, to create tens of thousands of diverse compounds that can be tested or screened with in vitro assays to identify potential valuable candidates. Chapter 1 gives a general overview of vHTS techniques and algorithms with particular emphasis to those methods that will be used later in the following chapter.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin